Currency Substitution in Developing Countries : An Introduction - Calvo, Guillermo (IMF Working Papers; Working Paper, 1992)
This paper reviews the main policy and analytical issues related to currency substitution in developing countries. The paper discusses, first, whether currency substitution should be encouraged or not; second, how the presence of currency substitution affects the choice of nominal anchors in inflation stabilization programs; third, the effects of changes in the rate of growth of the money supply on the real exchange rate; fourth, the interaction between inflationary finance and currency substitution; and, finally, issues related to the empirical verification of the currency substitution hypothesis.